2015
DOI: 10.1002/anie.201504887
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid, Amplification‐Free, and Sensitive Diagnostic Assay for Single‐Step Multiplexed Fluorescence Detection of MicroRNA

Abstract: The importance of microRNA (miRNA) dysregulation for the development and progression of diseases and the discovery of stable miRNAs in peripheral blood have made these short-sequence nucleic acids next-generation biomarkers. Here we present a fully homogeneous multiplexed miRNA FRET assay that combines careful biophotonic design with various RNA hybridization and ligation steps. The single-step, single-temperature, and amplification-free assay provides a unique combination of performance parameters compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
153
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 32 publications
1
153
0
Order By: Relevance
“…MicroRNAs (miRNAs) are recognized as critical regulators of multiple biological processes in cancer, breast cancer in particular, including tumorigenesis, tumor progression, stress response, and drug resistance . Since miRNA discovery, increasing evidence has indicated their essential roles in tumor progression and metastasis; therefore, miRNAs have emerged as potential biomarkers for cancer diagnosis, prognosis, and/or treatment efficacy . Thus, it was shown that miRNA expression patterns correlate with breast cancer subtype and the hormone receptor status …”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are recognized as critical regulators of multiple biological processes in cancer, breast cancer in particular, including tumorigenesis, tumor progression, stress response, and drug resistance . Since miRNA discovery, increasing evidence has indicated their essential roles in tumor progression and metastasis; therefore, miRNAs have emerged as potential biomarkers for cancer diagnosis, prognosis, and/or treatment efficacy . Thus, it was shown that miRNA expression patterns correlate with breast cancer subtype and the hormone receptor status …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a plethora of novel assay concepts for measurement of miRNAs has been published, including formats based on multiplexed Förster or flourescence resonance energy transfer (FRET) and quantum dot assay designs [116][117][118], and ligation-mediated hybridization to microarrays [119], respectively. It remains to be elucidated if any of these methods can take the next step to move into the clinical routine.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…[13][14][15] Fluorescence resonance energy transfer (FRET), in which the electronic excitation energy of an energy donor chromophore is transferred to an energy acceptor in the presence of a target, has been used previously in miRNA detection. [16][17][18] Traditional fluorophores used in FRET-based detection include Cy5, FAM and Texas red. However, these are limited by intrinsic drawbacks including broad emission bands and photobleaching effects.…”
Section: Introductionmentioning
confidence: 99%